Sosialisasi Stop Bullying Offline dan Online sebagai Upaya Menciptakan Lingkungan Sekolah Ramah Anak di SMP Negeri 1 Lotu - Lase, Justin Foera-era; Zebua, Meniati; Lase, Lilis Febrika Putri; Waruwu, Rani Sastri; Bate’e, Juni For Enjelina; Halawa, Diana; Giawa, Kasihani; Gulo, Neni Kurnia; Mendrofa, Hengkiwan; Gulo, Selmanto (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Bullying and cyberbullying remain challenges in creating a safe and child-friendly school environment, including at SMP Negeri 1 Lotu. The results of the needs assessment indicate that verbal bullying behavior still occurs frequently, accompanied by a low understanding of some students regarding cyberbullying. Therefore, this community service activity aims to describe the implementation and evaluate the impact of offline and online stop bullying socialization in improving students’ understanding of the forms, impacts, and efforts to prevent bullying. The novelty of this program lies in the integration of offline bullying and cyberbullying materials in a series of socializations and the involvement of members of the Intra-School Student Organization (OSIS) as pioneers of anti-bullying in the school environment. The activity uses a descriptive approach by combining qualitative data from observations and descriptive quantitative data obtained through pre-tests and post-tests of 45 OSIS members selected using a purposive sampling technique. The intervention was implemented through material delivery, interactive discussions, simulations, and learning evaluations. The results of the activity showed an increase in participants’ understanding of all indicators after participating in the socialization, supported by high participant participation during the activity. These findings indicate that the outreach program positively contributes to increasing students’ understanding of bullying and cyberbullying and supports preventive efforts to create a safe, inclusive, and child-friendly school environment.